Normative Analysis of Foreign Medical and Health Worker Policies in Indonesia and Their Impact on the National Health System - Yohan Edward Marpaung; Arman Lany (Jurnal Iman dan Spiritualitas, 2026)
This study examines the coherence and policy rationale of Indonesia’s utilization of foreign medical and health personnel (FMHP) under Government Regulation No. 28 of 2024 within the framework of the National Health System (NHS). The analysis focuses on the role of this policy as a transitional instrument to address priority referral service gaps while strengthening national health workforce capacity. Key concepts include health system governance, credentialing and clinical privileging, patient safety, informed consent, and the WHO health system building blocks. Employing a normative juridical (doctrinal legal research) method, this study applies statutory, conceptual, and systemic approaches. The scope of analysis covers health legislation, cross-sectoral labor and immigration regulations, and strategic NHS policy documents. Legal norms are examined through grammatical, systematic, and teleological reasoning and mapped against NHS output and outcome indicators. The findings demonstrate that, at the normative level, the FMHP policy is coherently designed in line with global health governance principles and oriented toward patient protection and capacity building. Nonetheless, implementation challenges persist, particularly regarding regional disparities in institutional capacity, inconsistent credentialing practices, cross-cultural communication barriers, and the absence of measurable indicators for technology transfer. The study recommends strengthening operational governance through the Deficit–Impact–Duration framework and a Technology Transfer Scorecard to ensure evidence-based evaluation. This research advances health law scholarship by integrating normative legal analysis with health system performance frameworks and proposing practical evaluative tools for assessing foreign health workforce policies as instruments of sustainable national capacity building.